Learning a novel rhythmic stepping task in children with probable developmental coordination disorder. (February 2023) - Inacio, Mario; Esser, Patrick; Weedon, Benjamin David; Joshi, Shawn; Meaney, Andy; Delextrat, Anne; Springett, Daniella; Kemp, Steve; Ward, Tomas; Izadi, Hooshang; Johansen-Berg, Heidi; Dawes, Helen
Abstract: Background: Developmental coordination disorder affects approximately 6% of children, interfering with participation in physical activity and can persist through adulthood. However, no studies have investigated the neuromotor mechanisms of learning of a novel task with rhythmic cueing. Methods: Movement Assessment Battery for Children-2nd edition was used to identify 48 children with probable developmental coordination disorder (13.9 ± 0.05 yrs., 27% male) and 37 typically developed (13.9 ± 0.10 yrs., 54% male). While instrumented with an inertial measurement unit, both groups performed a novel rhythmic stepping task and with a concurrent auditory stroop test (dual-task), underwent seven weeks of intervention with step training with rhythmic cuing and were tested for retention five weeks post-intervention. Findings: Initially, the group with probable developmental coordination disorder had a higher variability of step timing (coefficient of variation: 0.08 ± 0.003-typically developed – 0.09 ± 0.004-probable developmental coordination disorder, p < 0.05) and a frequency of peak power spectral density further from the target 0.5 Hz (0.50 ± 0.002 Hz-typically developed – 0.51 ± 0.003 Hz-probable developmental coordination disorder, p < 0.05), and were more affected by the dual-task: power spectral density at 0.5 Hz (−7.2 ± 3.3%-typically developed – -13.4 ± 4.6%- prob_DCD, p < 0.05) and stroop test errors (6.4 ± 1.1%-typically developed – -11.1 ± 2.4%- probable developmental coordination disorder, p < 0.05). The intervention led to similar improvements in both groups in coefficient of variation of step timing (0.12 ± 0.01-Pre – 0.07 ± 0.002-Post, p < 0.05), frequency of the peak power spectral density (0.51 ± 0.005 Hz-Pre – 0.50 ± 0.001 Hz-Post, p < 0.05) and relative power spectral density bandpower (3.2 ± 0.2%-Pre – 5.9 ± 0.3%-Post, p < 0.05). All improvements were retained after five weeks post-training. Interpretation: Rhythmic cueing shows strong promise for enhancing motor learning in children with probable developmental coordination disorder. Trial registration: Retrospectively registered on ClinicalTrials.gov with reference: NCT03150784 Highlights: Children with probable Developmental Coordination Disorder have impaired stepping. These deficits are expressed in spatiotemporal and spectral parameters. Cognitive concurrent tasks exacerbate these limitations. This population shows improvements after a rhythmic visual cueing intervention.